Ustaz Cool, Ustazah Trendy: Chiselled Islamic Celebrity Preachers - Rozita Abdullah; Kamaluddin Nurdin Marjuni; Rosidayu Sabran; Mohd Faizal Kasmani; Noor Adzrah Ramle; Mohd Yahya Mohamed Ariffin (Universiti Sains Islam Malaysia, 2024)
Islamic televangelism, arguably has become a staple in the Malaysian media environment today. The intensification of this genre has provided rise to personalities known as celebrity preachers. These celebrities are increasingly getting viewers’ and online followers’ attention which implies that this phenomenon needs a scholarly attention. This study, examines the insights of the production of Islamic televangelism programs to gain details on the ‘birth’ of celebrity preachers. In depth interviews were conducted with industry professionals and insiders to understand the nature of the production of Islamic televangelism. The discussion with the industry insiders reveals the conceptions of celebrities are wedged between television economy and culture.